Taxonomic reinstatement of Allium edentatum (Amaryllidaceae) and synonymization of A. brevipedicellatum based on integrative morphological and molecular evidences - Cheng, Rui-Yu; Huang, De-Qing; Tan, Jin-Bo; He, Xing-Jin; Xie, Deng-Feng (Phytotaxa, 2026)
This study formally reinstates Allium edentatum as an independent species from the Helan Mountains based on comprehensive morphological and molecular phylogenetic evidence, and treats A. brevipedicellatum as its later synonym. Morphological comparison reveals that A. edentatum closely resembles A. bidentatum but can be clearly distinguished by several key characters, including extremely short or nearly absent pedicels, ovate and toothless inner filaments at the basal half, a subglobose ovary with a tuberculate outer wall, and leaves with prominent longitudinal grooves and fine ridges. Phylogenetic analyses of 160 nuclear ribosomal ITS sequences strongly support A. edentatum as a monophyletic clade sister to A. bidentatum and A. bellulum within section Rhizomatosa. Integrating morphological and molecular data, we clarify the systematic position of A. edentatum and resolve its taxonomic status. Furthermore, we hypothesize that A. edentatum originated through geographic isolation and local adaptation during multiple climatic cycles of the Pleistocene, with its current distribution representing a potential relict of interglacial refugia. This study not only confirms the taxonomic validity of A. edentatum as an independent species but also refines the classification of sect. Rhizomatosa by providing an exhaustive identification key for all constituent taxa.